Engineering Properties of Silty Soil Stabilized with Lime and Rice Husk Ash and Reinforced with Waste Plastic Fiber - Agus Setyo Muntohar, Anita Widianti, Edi Hartono, and Wilis Diana (American Society of Civil Engineers., 2013)
Although abundant plastic waste contaminating the environment may be utilized as reinforcing materials, a potential pozzolanic material (rice husk ash blended with lime) possesses superior properties in stabilizing soils. Engineering behavior of the stabilized clayey/silty soil reinforced with randomly distributed discrete plastic waste fibers is investigated in this paper. The results indicate that the proposed method is very effective to improve the engineering properties of the clayey/silt soil in terms of compressive, tensile, and shear strength, which further enhanced the stability and durability of the soil. Based on the compressive strength, California bearing ratio (CBR), shear strength, and failure characteristics, the optimum amount of fiber mixed in soil/lime/rice husk ash mixtures ranges from 0.4–0.8% of the dry mass.